Studi Sifat Impak Ketahanan Aus dan Koefisien Gesek Bahan Komposit Arang Limbah Serbuk Gergaji Kayu Glugu Dengan Matrik Epoxy - I Gusti Ketut Puja (Jurnal Energi Dan Manufaktur, 2010)
Waste of sawdust materials of coconut wood is potential to be used as engineering materials of technology products, such asbrake pad for light vehicle. Some important properties of materials to be used as a brake pad is wear resistance, impactstrength and the friction coefficient. This study aims to investigate the coefficient of friction, wear and impact properties ofcomposite materials of coconut wood charcoal sawdust with epoxy matrix. Coconut wood charcoal sawdust produced attemperatures varies from 200, 300, 400 and 500 degrees Celsius for 2 hours respectively. The charcoal was tested for carboncontent. The charcoal with high carbon content then is used as filler composites. Composite is manufactured by hydraulic presscast method with content of filler (particle) varies from 28, 37, 46 and 55 percent (v/v). Testing was conducted on the coefficientof friction, wear, and Charpy impact. The results are verified with the properties of the commercial brake pad. Charcoal isproduced at a temperature of 200 and 300 degrees Celsius has the highest carbon content (91.98% and 89.64%). Compositefriction coefficient increases with increasing particle content. The largest friction coefficient (0.445) occurred in the compositewith particles content about 55 percent (v/v). Composite friction coefficient increases with increasing content of particleswhere the value is greater than the commercial brake pad (0.34). Composite with particle content of 46 percent has the lowestspecific wear rate, about 4.13 mm2/kg (the best wear resistance). This value still higher than the commercial brake pad (2.04mm2/kg). Composite with particles content of 37 percent has the fracture energy about 0.27 joules, and the thoughness about2.87 kJ/mm2. Composite with particle content of 37 percent was likely can as a brake pad, but the wear resistance still lowerthan the commercial products